2006
DOI: 10.1111/j.1460-9568.2006.04602.x
|View full text |Cite
|
Sign up to set email alerts
|

A local GABAergic system within rat trigeminal ganglion cells

Abstract: We investigated the GABAergic system within the Sprague-Dawley rat (2-3-weeks old) trigeminal ganglion (TG). Reverse transcription-polymerase chain reaction (RT-PCR) analysis revealed expression of glutamate decarboxylase (GAD) 65 and GAD67 mRNAs and mRNAs encoding GABA(A) receptor subunits alpha1-6, beta1-3, gamma1-3, and delta. In situ hybridization revealed that GAD65 and GAD67 mRNAs were expressed in neuronal cell bodies but not satellite cells. Immunohistochemical analysis showed that only GAD65 was expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 66 publications
(99 reference statements)
7
74
0
Order By: Relevance
“…It is possible that the fibers in the more lateral areas of the hindbrain mediate the lateral activity that is synchronized with the midline activity, and that sensory input from caudal hindbrain or spinal cord influences SA in the hindbrain. GAD expression is observed in early postnatal trigeminal motor neurons (Turman et al, 2001) and trigeminal ganglion cells (Hayasaki et al, 2006). The presence of both GABAergic and serotonergic axons within the hindbrain midline commissural region suggests that either or both may mediate excitation of the hindbrain initiation.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the fibers in the more lateral areas of the hindbrain mediate the lateral activity that is synchronized with the midline activity, and that sensory input from caudal hindbrain or spinal cord influences SA in the hindbrain. GAD expression is observed in early postnatal trigeminal motor neurons (Turman et al, 2001) and trigeminal ganglion cells (Hayasaki et al, 2006). The presence of both GABAergic and serotonergic axons within the hindbrain midline commissural region suggests that either or both may mediate excitation of the hindbrain initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GABA, that is released in Ca 2? -independent manner as suggested in TG (Hayasaki et al 2006), may regulate basal threshold levels of the nodose ganglion cells. In conclusion, the satellite cells may regulate threshold level of ganglion neurons via glutamate and GABA mediated systems.…”
Section: Effect Of Endogenous Gaba In Ngmentioning
confidence: 92%
“…Hayasaki et al (2006) demonstrated that TG neuronal cell bodies express GABA, GAD, and functional GABA A receptors, and that satellite cells express GABA, suggesting the existence of a local GABAergic system within TG. Furthermore, it has been reported that GABA has an analgesic effect via GABA A receptors in TG neurons in mice that undergo injection of the GAD65 gene into satellite cells (Vit et al 2009) and that GABA inhibits the excitatory effects of ATP via GABA A receptors in DRG neurons (Sokolova et al 2001).…”
Section: Introductionmentioning
confidence: 98%
“…One and 5 μg of RNA (DRG and spinal cord, respectively) was reverse-transcribed into cDNA using Superscript II (Invitrogen). Primers for GAD67 8 and β-actin (Ambion, Austin, Texas) were used: GAD67 forward primer, 5′-GCTGGAAGGCATGGAAGGTTTTAA-3′; reverse primer, 5′-AATATCCCATCACCATCTTTATTTGACC-3′. The GAD67 and β-actin mRNA level was quantified with an MX3000P real-time PCR system (Stratagene, La Jolla, California) in a 25 μl volume using SYBR Green PCR Master Mix (QIAGEN, Valencia, California).…”
Section: Quantification Of Gad67 Mrnamentioning
confidence: 99%